ChemInform Abstract: Economical Synthesis of Cyclic Carbonates from Carbon Dioxide and Halohydrins Using K2CO3. Issue 49 (17th November 2016) - Hirose, Takuji; Shimizu, Shinsuke; Qu, Shujie; Shitara, Hiroaki; Kodama, Koichi; Wang, Lin
Abstract: A highly simple, economical, and selective synthesis of five‐membered cyclic carbonates is achieved by the reaction of CO2 with 1, 2‐halohydrins in the presence of K2 CO3 .